Impact of institutional quality on the capital structure of firms in developing countries - Md Nasir, Annuar (Elsevier BV, 2019)
This paper investigates the effects of institutional quality on firms' capital structure for a panel of 3891 firms from 23 developing countries. Our main findings for the full panel show institutional quality has a significantly positive effect on firms' capital structure. At the regional level, based on the panel data for 2187 firms from Asian countries and 1091 firms from Latin American and Eastern European countries, institutional quality has a significantly positive effect on capital structure. However, for the 613 firms from African countries, institutional quality is mostly insignificant. Additional analysis reveals positive effects of legal enforcement on capital structure